Preparation of SnO2/carbon composite hollow spheres and their lithium storage properties - Lou, David Xiong Wen (2012)
In this work, we present a novel concept of structural design for preparing functional composite hollow spheres and derived double-shelled hollow spheres. The approach involves two main steps: preparation of porous hollow spheres of one component and deposition of the other component onto both the interior and exterior surfaces of the shell as well as in the pores. We demonstrate the concept by preparing SnO2/carbon composite hollow spheres and evaluate them as potential anode materials for lithium-ion batteries. These SnO2/carbon hollow spheres are able to deliver a reversible Li storage capacity of 473 mA h g^−1 after 50 cycles. Unusual double-shelled carbon hollow spheres are obtained by selective removal of the sandwiched porous SnO2 shells.